Muc5b-deficient mice develop early histological lung abnormalities - Valque, Hélène (Biol Open, 2019)
Gel-forming mucins are the main organic component responsible for physical properties of the mucus hydrogels. While numerous biological functions of these mucins are well documented, specific physiological functions of each mucin are largely unknown. To investigate in vivo functions of the gel-forming mucin Muc5b, which is one of the major secreted airway mucins, along with Muc5ac, we generated mice in which Muc5b was disrupted and maintained in the absence of environmental stress. Adult Muc5b-deficient mice displayed bronchial hyperplasia and metaplasia, interstitial thickening, alveolar collapse, immune cell infiltrates, fragmented and disorganized elastin fibers and collagen deposits that were, for approximately one-fifth of the mice, associated with altered pulmonary function leading to respiratory failure. These lung abnormalities start early in life, as demonstrated in one-quarter of 2-day-old Muc5b-deficient pups. Thus, the mouse mucin Muc5b is essential for maintaining normal lung function.